The Influence of Rural Irrigation Infrastructure on Rice Production in East Java, Indonesia: Rural Irrigation and Rice Production (Journal of Tropical Rural Development, 2024)
Background and purpose – Rice production plays a crucial role in achieving national food security. Adequate water supply through reliable irrigation systems is essential for crop production, especially for farmers. Therefore, infrastructure development, particularly irrigation, is vital in supporting rice production. This study aims to describe the level of rice production in East Java and analyze the influence of the proportion of irrigated rice fields, fertilizer distribution factors, and rainfall on rice production in East Java. Methodology – This research uses a quantitative approach with panel data regression analysis techniques. The data used in this study are secondary data obtained from the Department of Agriculture and Food Security of East Java Province and the Central Statistics Agency (BPS) from 2013 to 2017, covering 10 regencies/cities in East Java. Findings – This study found that the proportion of irrigated rice fields does not significantly impact rice production, suggesting a decline in the functionality of irrigation networks. This inefficiency in water use disrupts both rice production and the performance of irrigation infrastructure. In contrast, the distribution of fertilizer and rainfall significantly influence rice production. Improved fertilizer distribution enhances farmers' access to urea, meeting crop nutritional needs, while adequate rainfall is crucial for rice plant growth and preventing crop failure. Implications – better management of irrigation infrastructure, along with efficient fertilizer distribution and rainfall management, can substantially improve rice production in East Java.